Coprescription of Levodopa with Antipsychotics in a Population of 84 596 Psychiatric Inpatients from 1994 to 2008 - Haueis, P.; Russmann, S.; Zorina, O. I.; Grohmann, R.; Kullak-Ublick, G. A.; Jaquenoud Sirot, E.; Russmann, H. (Pharmacopsychiatry, 2012)
Patients on levodopa therapy frequently require additional antipsychotic pharmacotherapy. However, consideration must be given to antagonistic interactions on dopamine receptors between levodopa and antipsychotics, and efficacy and safety of such combinations. We therefore aimed to explore the practice and rationale of coprescription between levodopa and antipsychotics in psychiatric patients.A descriptive retrospective study based on cross-sectional prescription data repeatedly collected from psychiatric inpatients through the international Drug Safety in Psychiatry (AMSP) program between 1994 and 2008 was undertaken.Within a population of 84 596 psychiatric patients the prevalence of levodopa therapy was 1.0% (n=886). Among those patients on levodopa therapy 59.6% (n=528) also received antipsychotics. Quetiapine coprescription increased after its first marketing in 2000 to 45.9% in 2008. Coprescription of clozapine and olanzapine decreased from up to 25 and 22%, respectively, before to less than 10% after the introduction of quetiapine. Coprescribing of other antipsychotics remained approximately stable with average prevalences between 6 and less than 1%.Quetiapine has now replaced clozapine as the most frequently coprescribed neuroleptic in psychiatric patients with levodopa therapy. This is in accordance with recent data indicating a low potential for clinically relevant interactions with levodopa and efficacy against psychosis in levodopa-treated patients. The combined use of antipsychotics other than quetiapine and clozapine with levodopa is less common and generally not supported by appropriate evidence.
Keywords: antipsychotics; drug interactions; levodopa; Parkinson’s disease; restless legs syndrome; pharmacoepidemiology